2020
DOI: 10.3390/brainsci10100682
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cortisol Levels Are Associated with Craving and Cognitive Performance in Cocaine-Abstinent Subjects: A Pilot Study

Abstract: Cortisol is a glucocorticoid hormone secreted by the adrenal cortex upon the activation of the hypothalamic-pituitary-adrenal (HPA) axis. Assessment of cortisol in saliva has emerged as a reliable way of evaluating HPA function. We examined the relationships between salivary cortisol levels with both craving and cognitive performance, as a possible biomarker of cocaine addiction. Cognitive performance (attention, declarative and working memory, executive functions and recognition of emotions) was assessed in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Ligabue et al observed that increased cortisol levels at inpatient treatment entry were predictive of early treatment dropout before the scheduled 14 days of inpatient stay [ 68 ]. Furthermore, Sampedro-Piquero et al showed that a higher salivary morning cortisol concentration was associated with CUD severity factors (duration of the disorder and craving scores) [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligabue et al observed that increased cortisol levels at inpatient treatment entry were predictive of early treatment dropout before the scheduled 14 days of inpatient stay [ 68 ]. Furthermore, Sampedro-Piquero et al showed that a higher salivary morning cortisol concentration was associated with CUD severity factors (duration of the disorder and craving scores) [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ligabue et al highlighted a negative relationship between the salivary cortisol concentration and retention in a withdrawal program in cocaine users [ 68 ], suggesting a dysregulation of the HPA axis. Furthermore, a significant positive correlation between morning cortisol levels and craving levels in abstinent cocaine users has been demonstrated [ 69 ]. Additionally, the cortisol level could be an interesting biomarker to predict the risk of relapse in CUD patients and in cocaine users, as salivary cortisol would probably be easier to measure than plasma cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…attention, short-term memory, working memory, and executive functioning of the brain. 20 Environment has an impact on one's ability to remain attentive in their task and retain information received. The source of distraction can be internal factors (i.e.…”
Section: Discussionmentioning
confidence: 99%